Pier Paolo Pasolini : Contemporary Perspectives - Testa, Bart; Rumble, Patrick Allen, 1963- (Book collections on Project MUSE., 1994)
A reexamination of Pasolini life and work as a poet, novelist, filmmaker, journalist and cultural theorist reflecting new developments in semiotics, post-structuralist theory, and historical research on Italian literature and film.